Alex Ferguson : My Autobiography - Ferguson, Alex (London Hodder & Stoughton, 2013)
The celebratory, revealing, inspiring and entertaining autobiography of the greatest manager in the history of British football.
Include Color Illustrations and Index
Keywords: Soccer managers -- Manchester United (Soccer team) -- Scotland -- Great Britain